1998
DOI: 10.7863/jum.1998.17.11.693
|View full text |Cite
|
Sign up to set email alerts
|

Lower extremity deep venous thrombosis in cancer patients: correlation of presenting symptoms with venous sonographic findings.

Abstract: ancer patients are at increased risk for the development of DVT. The clinical sequelae of DVT in this population are significant. In addition to the prolonged discomfort and swelling associated with chronic DVT, the presence of acute femoropopliteal DVT poses a grave risk of thromboembolic complications. Pulmonary embolism is a frequent cause of death among cancer patients. 1 Early diagnosis and treatment of DVT is vital to decrease these complications.Lower extremity deep venous sonography using compression a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 11 publications
0
6
0
1
Order By: Relevance
“…This result differs from another study where unilateral edema was the most common presentation of edema as a clinical sign suggesting underlying thrombosis in cancer patients. 8 However, the same study identified that 12/26 (46 percent) of patients with asymmetric bilateral edema also had a DVT. In a prospective study to determine the prevalence and associated variables of DVT in 258 hospice inpatients with advanced cancer, the majority of patients with DVT in one leg only had bilateral swelling.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…This result differs from another study where unilateral edema was the most common presentation of edema as a clinical sign suggesting underlying thrombosis in cancer patients. 8 However, the same study identified that 12/26 (46 percent) of patients with asymmetric bilateral edema also had a DVT. In a prospective study to determine the prevalence and associated variables of DVT in 258 hospice inpatients with advanced cancer, the majority of patients with DVT in one leg only had bilateral swelling.…”
Section: Discussionmentioning
confidence: 94%
“…10 Often bilateral edema is attributed to the underlying malignancy, treatment for the malignancy, or other clinical, metabolic, or endocrine disorders, and, more rarely, DVT. 8,[11][12][13][14] Thus, a DVT may be masked or misdiagnosed. 12,15 Our study supports the recommendation made by Loud and colleagues 8 that a difference in the degree of lower extremity edema should alert the clinician to an increased likelihood of DVT.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Malignancy recurrence or posttreatment procedures, such as irradiation and/or surgery, can also lead to lymphatic obstruction. Vasogenic edema in malignancy is either related to venous stasis in the vessel lumen or a result of external tumor compression [2, 3]. …”
Section: Introductionmentioning
confidence: 99%